A concise synthesis of chiral indanes as α1A adrenoceptor partial agonists. Issue 47 (25th November 2015) - Roberts, Lee R.; Corbett, Matthew S.; Fussell, Steven J.; Hitzel, Laure; Jessiman, Alan S.; Mason, Helen J.; Osborne, Rachel; Ralph, Michael J.; Stennett, Adam S.D.; Wheeler, Simon; Storer, R. Ian
Graphical abstract: Abstract: The synthesis of a series of chiral indanes with reported α1A partial agonist activity is outlined, applying a rhodium catalysed cyclisation for template construction. This method was extended to the asymmetric synthesis of lead compound PF-03774076 (1 ) which was prepared on >20 g scale in seven steps. Highlights include Rh-mediated cyclocarbonylation and an asymmetric alkene hydrogenation.